Between ‘minjung’ and ‘literature’: Korean labor poetry and reportage literature in the 1980s - Kim, Nahyun (International Journal of Korean Humanities and Social Sciences, 2022)
This paper reviews three books which symbolically represent a new direction in ‘minjung literature’ in the 1980s. Labor poet Park No-hae (박노해)’s collection of poems, Dawn of Labor (노동의 새벽), was popular when it was published because it was literature in the form of poetry written by a real member of the minjung who kept his identity as a worker secret by becoming a faceless poet. Song Hyo-soon (송효순)’s memoir, Road to Seoul (서울로 가는 길) records the miserable reality of factories as the subaltern writing. Park Tae-soon (박태순)’s The Land and the Minjung (국토와 민중) was reportage (reporting) literature that records his travels around the country. He shows that the history of ‘minjung’ physically exists within the country and testifies that the land was owned by the ‘minjung’. These three books reflect how ‘minjung literature’ in the 1980s testified to the ‘minjung’. Concern about how to describe and represent the ‘minjung’ shows thoughts about both the ‘minjung’ and literature. The ‘minjung’ testimonies written in a variety of literary styles cause readers to ask themselves what literature is. ‘Minjung’ poetry poetry and reportage in the 1980s can help answer this question.